Phylogenetic relationships of Lygodactylus geckos from the Gulf of Guinea islands: rapid rates of mitochondrial DNA sequence evolution? - Jesus, José (2022)
Mitochondrial DNA (12S rRNA, 16S rRNA and cytochrome b) sequences and nuclear sequences (C-mos) were analysed within Lygodactylus thomensis from three volcanic islands in the Gulf of Guinea that have never been connected to the continent. Our aim was to assess interrelationships between the three subspecies to test a recent hypothesis suggesting high rates of mitochondrial DNA (mtDNA) sequence evolution in geckos. Our results indicate, based on mtDNA sequence data, that the three subspecies are genetically differentiated at a level more typically observed between species. However, the forms cannot be differentiated using the nuclear marker C-mos. These results further substantiate the hypothesis of rapid rates of mtDNA sequence evolution in geckos, although the alternative that C-mos is evolving more slowly cannot be discounted. They also suggest that present calibrations for molecular clocks are at the upper limit of divergence over time.